Explaining the rise of third-party funding in investment arbitration - Florence Dafe; Zoe Williams (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
This Perspective examines explanations for the emergence of TPF in ISDS, including key domestic legal changes, efforts to ensure greater "access to justice", and developments in the global financial system. The authors argue that understanding the emergence of TPF helps us better anticipate its effect on the investment regime.
Keywords: 330